Concentrações séricas de progesterona e metabólitos lipídicos em cabras mestiças alimentadas com dietas hiperlipídicas durante o ciclo estral - Uribe-Velásquez, Luis Fernando [UNESP] (1997)
The serum concentration of progesterone and lipidics metabolites were studied using tallow as lipidic suplementation during the estrous cycle of 32 crossbred goats, with average age and weight of five months and 25 kg. The goats were randomlly allocated in four treatments as described: treatment 1, restricted intake; treatment 2, full feed; treatments 3 and 4, hiperlipidics diets with 2.5% and 5.0% of tallow, respectively. The female goats under restricted intake, showed the small serum progesterone level (P<0.05) at 0, 3, 6, 9 and 12 days of the estrous cycle, while the ones under hiperlipidics diets, treatments 3 and 4, showed greater levels. The same results were found for serum levels of cholesterol and HDL in the estrous cycle days 6, 9 and 21, and 12, 15 and 21, respectively, that is, the females under restricted diet showed the small level and the ones treated with hiperlipidics diets, the highest. The hiperlipidics diets were important factor in altering the serum cholesterol and HDL levels, showing that the lipidic metabolism may be effective in cyclic luteal progesterone production in the puberal female goats.